Solubility of CO2 in molten Li2CO3-LiCl - Hu, Xianwei; Deng, Wentao; Shi, Zhongning; Liu, Aimin; Yu, Jiangyu; Wang, Zhaowen (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
Solubility of CO2 in molten Li2CO3-LiCl was measured by using a pressure differential method and the enthalpy change of the dissolution was calculated on that basis. The relationships between the solubility and the enthalpy change, and the temperature and the composition of the melts were discussed. The results showed that when the temperature was 873–923 K and the Li2CO3 content was 10–50 mol%, the solubility of CO2 increased with decreasing temperature and/or increasing Li2CO3 content.The maximum solubility was 3.965 × 10−7gCO2/gmelt at 873K when the content of Li2CO3 was 50 mol%. The dissolution of CO2 was endothermic. With increasing temperature and Li2CO3, more energy was needed for CO2 dissolution.